2015
DOI: 10.1186/s40711-015-0010-1
|View full text |Cite
|
Sign up to set email alerts
|

Capital with beliefs—a study of charitable donations of private business owners in Wenzhou, China

Abstract: Borrowing Weber's dual-interest model and "switchman" hypothesis, this study uses survey data to analyze the internal driving force and diversity in the charitable giving behaviors of private business owners from Wenzhou, China. The study found that (1) the political and religious beliefs of business owners can have a positive influence on donation behaviors; (2) there are significant differences in the direction, form, and consequences of the donation due to differences in these beliefs, highlighting the sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
4
0
1
Order By: Relevance
“…There are many examples of how entrepreneurs’ CPC membership negatively affected their cooperation with foreign firms. For example, a 2011 survey of Chinese private entrepreneurs showed that a majority of the interviewed entrepreneurs with communist beliefs expressed a negative attitude toward foreign capitalism but embraced market practices (Zhou and Hu, 2015), as did Mingshan Yin—founder of the large motorcycle and automobile manufacturer Lifan Group ( The Economist , 2003). These prior studies and examples suggest that the communist ideological imprint is still functioning, even though it is incongruent with the current business environment and detrimental to an organization’s survival and success by constraining its attempts to adapt to and profit from the changing environment.…”
Section: The Effects Of Ideological Imprinting On Entrepreneurs’ Decimentioning
confidence: 99%
“…There are many examples of how entrepreneurs’ CPC membership negatively affected their cooperation with foreign firms. For example, a 2011 survey of Chinese private entrepreneurs showed that a majority of the interviewed entrepreneurs with communist beliefs expressed a negative attitude toward foreign capitalism but embraced market practices (Zhou and Hu, 2015), as did Mingshan Yin—founder of the large motorcycle and automobile manufacturer Lifan Group ( The Economist , 2003). These prior studies and examples suggest that the communist ideological imprint is still functioning, even though it is incongruent with the current business environment and detrimental to an organization’s survival and success by constraining its attempts to adapt to and profit from the changing environment.…”
Section: The Effects Of Ideological Imprinting On Entrepreneurs’ Decimentioning
confidence: 99%
“…17 Their main finding was that political connection has a statistically significant positive correlation with charitable giving. A fourth study is that of Zhou and Hu (2015), who studied the charitable giving behaviour of private business owners in Wenzhou using data collected in 2011 and who reported that owners with religious believes and those taking part in religious activities tend to donate more than others. This study also reported that the existence of a party organization at the firm level affects donation behaviour.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, trust in charities denominates donors’ perception of non-commercial and charity activities like fundraising campaigns to ensure that charities are honest and involve the affected parties in the process (Alhidari et al , 2018). On the other hand, ethics denote cultural, religious, social and human aspects of the donors that motivate them to raise the funds to mitigate the pandemic impact (Zhou and Hu, 2015). In this regard, five items were used to measure charity projects and trust in charities, four questions for attitude toward fundraising and six questions for the ethical factor adapted from (Bin-Nashwan et al , 2020; Sarea and Bin-Nashwan, 2020).…”
Section: Methodsmentioning
confidence: 99%